The Shanghai Cooperation Organization after Enlargement: New Challenges and Prospects - D. V. Efremenko (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper examines new challenges that confront the Shanghai Cooperation Organization (SCO) after India and Pakistan have joined it as full-fledged members. This enlargement of the SCO implies a considerable increase in its political and economic weight, as well as additional interstate contradictions, which have previously had a peripheral significance for the SCO.In that regard special attention is drawn to the new political dynamics within the SCO. The author argues that cooperation within the Russia-India-China triangle (RIC) will play a decisive role for the SCO development. In this context, two scenarios are outlined. The first one envisages that the Russo-Chinese and Russo-Indian relations will have a positive dynamics while the Chinese-Indian relations will remain troubled. It is stressed that India’s participation in the SCO is likely to become another factor which will prevent the evolution of the Organization into anti-Western geopolitical alliance. Under favorable conditions, all three powers will be able to formulate a common position with regard to the most crucial international issues or to respond promptly to negative tendencies in the economic and security spheres. The second scenario involves a gradual deepening and extension of cooperation in the RIC format based on a common vision of geopolitical transformations within the Greater Eurasia. In this case, it can be assumed that over time the SCO will become the basis for the formation of the Greater Eurasian Partnership.Another important topic covered in the paper is a security problem which is a traditional priority of the SCO policy in general and in the Central Asia region in particular. This issue has acquired new dimensions due to the Organization’s enlargement and the growth of its geopolitical role. In 2018–2019 the SCO powers, together and separately, have made a decisive contribution to the settlement of inter-Afghanistan conflict when the US and NATO troops had been withdrawn from Afghanistan. Moreover, it was due to the SCO efforts that the breakthrough of extremist and terrorist groups from Afghanistan to the Central Asia countries was prevented. The author concludes that in the coming years the SCO will play the key role in structuring the Greater Eurasia and strengthening the multipolar world order.